A study on the relationship between emotional intelligence and the quality of work life at Pejabat Tanah Dan Jajahan Machang / Siti Nursyuwaibah Mohamad Rashid - Mohamad Rashid, Siti Nursyuwaibah (Faculty of Business and Management, 2019)
The purpose of this study is to identify the relationship between emotional intelligence and quality of work life towards employees of Pejabat Tanah Dan Jajahan Machang. This study was descriptive and correlational research. The sample of the study was consisted of 63 respondents at Pejabat Tanah Dan Jajahan Machang who were selected through simple random sampling based on list name provided. The questionnaires consisted of the items regarding emotional intelligence and quality of work life was distributed to the respondents. The data then analyzed by using SPSS 22.0 software. In order to identify the objective of the study in which the factors of emotional intelligence, the highest and the lowest factor of emotional intelligence the result of descriptive statistic of mean and standard deviation was used. The relationship between emotional intelligence and quality of work life was identified through the result and outcomes of Pearson Correlations coefficient. Through the study, self-awareness, self-management, social awareness and relationship management was provided as the factors of emotional intelligence. The findings identify that all of the factors of emotional intelligence results in a positive strong relationship with quality of work life. Furthermore, results evident that, self-awareness as the highest factors and relationship management as the lowest factors of emotional intelligence towards quality of work life. The result of the study show, there was relationship between emotional intelligence and quality of work life towards employees of Pejabat Tanah Dan Jajahan Machang. This study was significant to employers, employees and also students in improving emotional intelligence among themselves as emotional intelligence can improve the quality of work life.